2005
DOI: 10.4049/jimmunol.175.12.8242
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-Induced Invasion and Angiogenesis of Gastric Cells Is Mediated by Cyclooxygenase-2 Induction through TLR2/TLR9 and Promoter Regulation

Abstract: Cyclooxygenase-2 (COX-2) plays a crucial role in Helicobacter pylori-associated gastric cancer. In this study, we report that H. pylori-induced COX-2 expression enhances the cancer cell invasion and angiogenesis via TLR2 and TLR9, which can be attenuated by the specific COX-2 inhibitor NS398 or celecoxib. The cAMP response element (CRE) and AP1 sites, but not κB on the COX-2 promoter, are involved in MAPKs-regulated COX-2 expression. Differential bindings of the CREB-1, ATF-2, c-jun to the CRE site, and the c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 48 publications
3
113
0
8
Order By: Relevance
“…Their role in carcinogenesis depends on the activation of NF-κB and related genes, resulting in the production of cytokines such as IL-1, IL-2, IL-6, IL-10 and TNF-α; the recruitment of cells of the immune system by chemokines; the maintenance of chronic inflammation; and suppression in the tumor microenvironment. This complex net of chemical and direct cell-to-cell interactions may contribute to tumor survival and progression through an antiapoptotic effect, the direct inhibition of cell cytotoxicity or angiogenesis [57,58]. There is still controversy regarding TLRs in angiogenesis, as to whether they promote or inhibit the formation of new vessels.…”
Section: The Results Of Tlr Activation -Tlrs In Carcinogenesismentioning
confidence: 99%
“…Their role in carcinogenesis depends on the activation of NF-κB and related genes, resulting in the production of cytokines such as IL-1, IL-2, IL-6, IL-10 and TNF-α; the recruitment of cells of the immune system by chemokines; the maintenance of chronic inflammation; and suppression in the tumor microenvironment. This complex net of chemical and direct cell-to-cell interactions may contribute to tumor survival and progression through an antiapoptotic effect, the direct inhibition of cell cytotoxicity or angiogenesis [57,58]. There is still controversy regarding TLRs in angiogenesis, as to whether they promote or inhibit the formation of new vessels.…”
Section: The Results Of Tlr Activation -Tlrs In Carcinogenesismentioning
confidence: 99%
“…Differential binding of CREB-1, ATF-2, and c-jun to the CRE site and c-fos, c-jun, and ATF-2 to the AP1 site were demonstrated and attenuated by different MAPK inhibitors as well as mutants of TLR2 and TLR9. In sum, these results showed that H. pylori activated TLR2 and TLR9 to activate MAKs, particularly p38, and downstream transcription factors (CREB-1, ATF-2, c-jun, and c-fos) resulting in activations of CRE and AP-1 on the COX-2 promoter (Chang et al, 2005).…”
Section: Toll-like Receptor Signaling In Tumor Angiogenesismentioning
confidence: 83%
“…Thus, H. Pylori activation of TLR2 and TLR9 signals activate the MAPK cascade leading to increased COX-2 and COX-2-dependent prostaglandin E 2 (PGE 2 ) release. This contributes to cancer cell invasion and angiogenesis (Chang et al, 2005). The COX-2 increase can be attenuated by the specific COX-2 inhibitor, NS398 or celecoxib.…”
Section: Toll-like Receptor Signaling In Tumor Angiogenesismentioning
confidence: 99%
“…H. pylori flagellin is a TLR5 agonist in vitro (11,16), whereas some conflicting reports show that H. pylori flagellin evades TLR5 recognition, which may contribute to its long-term persistence in hosts (19,20). TLR9 could recognize H. pylori CpG DNA, leading to the induction of cytokine secretion (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of the TLR pathway induces NF-kB activation and transcription of immune response genes such as cytokines and chemokines, leading to the activation of innate immunity and regulation of acquired immunity (9). To date, 10 members of the TLR family have been identified in humans (10), in which TLR2, 4, 5, and 9 are reported to be involved in H. pylori recognition (11)(12)(13)(14)(15)(16)(17)(18). TLR2 was shown to recognize H. pylori lipopolysaccharide (LPS) (11).…”
Section: Introductionmentioning
confidence: 99%